2014
DOI: 10.1016/j.cell.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

A Single Oncogenic Enhancer Rearrangement Causes Concomitant EVI1 and GATA2 Deregulation in Leukemia

Abstract: Chromosomal rearrangements without gene fusions have been implicated in leukemogenesis by causing deregulation of proto-oncogenes via relocation of cryptic regulatory DNA elements. AML with inv(3)/t(3;3) is associated with aberrant expression of the stem-cell regulator EVI1. Applying functional genomics and genome-engineering, we demonstrate that both 3q rearrangements reposition a distal GATA2 enhancer to ectopically activate EVI1 and simultaneously confer GATA2 functional haploinsufficiency, previously ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
552
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 592 publications
(589 citation statements)
references
References 51 publications
18
552
1
2
Order By: Relevance
“…It is of great interest to note that positioning of an enhancer element was noted by Suzukawa et al 51 back in 1994, but regrettably, the hypothesized enhancer element was wrongly proposed to be associated with RPN1 gene rather than the GATA2 gene because of the lack of further functional studies. 51 As clearly demonstrated by Gröschel et al, 59 there is no new fusion transcript generated, as had been previously thought. 51 By using a completely different approach, namely, bacterial artificial chromosome transgenic mouse model recapitulating the inv(3), Yamazaki et al 60 have shown that the transgenic mice only developed leukemias when EVI1 was ectopically activated by G2DHE, but this did not happen in mice missing GATA2 enhancer, further corroborating the findings by Gröschel and associates.…”
Section: New Discovery Of Reallocation Of Gata2 Distal Hematopoietic supporting
confidence: 59%
See 3 more Smart Citations
“…It is of great interest to note that positioning of an enhancer element was noted by Suzukawa et al 51 back in 1994, but regrettably, the hypothesized enhancer element was wrongly proposed to be associated with RPN1 gene rather than the GATA2 gene because of the lack of further functional studies. 51 As clearly demonstrated by Gröschel et al, 59 there is no new fusion transcript generated, as had been previously thought. 51 By using a completely different approach, namely, bacterial artificial chromosome transgenic mouse model recapitulating the inv(3), Yamazaki et al 60 have shown that the transgenic mice only developed leukemias when EVI1 was ectopically activated by G2DHE, but this did not happen in mice missing GATA2 enhancer, further corroborating the findings by Gröschel and associates.…”
Section: New Discovery Of Reallocation Of Gata2 Distal Hematopoietic supporting
confidence: 59%
“…As such, this enhancer is named G2DHE. Gröschel et al 59 have showed that the rearrangements of 3q21q26.2 in a form of inversion [inv(3)] or translocation [t(3;3)] result in reallocation of G2DHE to physically interact with the promoter of EVI1, leading to 2 simultaneous events: an ectopically activating EVI1 oncogene, and the concomitant loss of enhancer activity for endogenous GATA2 function with resultant GATA2 haploinsufficiency 59 ( Figure 3, C). It is of great interest to note that positioning of an enhancer element was noted by Suzukawa et al 51 back in 1994, but regrettably, the hypothesized enhancer element was wrongly proposed to be associated with RPN1 gene rather than the GATA2 gene because of the lack of further functional studies.…”
Section: New Discovery Of Reallocation Of Gata2 Distal Hematopoietic mentioning
confidence: 99%
See 2 more Smart Citations
“…Stefen et al analyzed 41 samples using targeted next generation sequencing (NGS), functional genomics and genome-engineering, with confirmed EVI1 overexpression and harboring an inv(3)(q21.3q26.2) or a t(3;3)(q21.3q26.2), including 38 primary bone marrow samples from patients, that is AML (n=33), chronic myeloid leukemia -blast crisis (CML-BC, n=2), and myelodysplastic syndromes (MDS, n=3), as well as three cell lines (MUTZ-3, molm-1 and UCSD-AML1). [1] The data showed that inv(3)/t(3;3) chromosomal rearrangements cause dysregulation of two specific AML predisposition genes, EVI1 and GATA2, by aberrant activity of a single enhancer element in its ectopic chromatin environment, without the formation of an oncogenic fusion product. The identified enhancer appears to originally control the transcription of 110 kb distant GATA2 gene at 3q21, and not the nearby gene RPN1.…”
mentioning
confidence: 99%